A MODIFIED CARBON PASTE ELECTRODE WITH TWO LAYERS OF POLY(GLUTAMIC ACID) FOR DETERMINATION OF URID ACID USING VOLTAMMETRIC TECHNIQUE - Amriana Sanusi, Syafitri
In this research, a square wave voltammetry technique for determination of uric acid has been developed using carbon paste electrode modified with two layers of poly(glutamic acid) as working electrode. The first layer attached to the surface of CPE was non imprinted poly(glutamic acid) (NIP) and the second layer was molecularly imprinted poly(glutamic acid) (MIP) layer attached to the NIP surface. The layers was deposited through electropolymerization process using cyclic voltammetry technique in the potential range of 800 to 2000 mV in phosphate buffer solution (pH 7). Calibration curve of uric acid has a good linearity in the concentration range of 0,01 – 0,1 mM with the detection limit of 2,27 ?M. Determination of uric acid in real sample showed very accurate results with percent recovery of 96,92 – 108,11 %.